The distance between two points (x1, y1) and (x2, y2) is given by D = `sqrt((x2 - x1)^2 + (y2 - y1)^2)`

The point R has the coordinates (-3, 2) and T has the coordinates (4, 1).

Substituting these values in the formula for distance, the length of RT is...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The distance between two points (x1, y1) and (x2, y2) is given by D = `sqrt((x2 - x1)^2 + (y2 - y1)^2)`

The point R has the coordinates (-3, 2) and T has the coordinates (4, 1).

Substituting these values in the formula for distance, the length of RT is `sqrt((4 + 3)^2 + (2 - 1)^2)`

=> `sqrt(7^2 + 1^2)`

=> `sqrt (49 + 1)`

=> `sqrt 50`

=> `5*sqrt 2`

**The length of RT is `5*sqrt 2` **